Pengaruh Ekstrak Etanol Buah Terong Belanda (Solanum betaceum Cav.) terhadap Penurunan Kadar Trigliserida pada Tikus Wistar dengan Dislipidemia - Syahira Multazami; Yuke Ireka; Welly ratwita (ACTA Medical Health Sciences, 2025)
Dyslipidemia, an abnormality in lipid metabolism marked by elevated triglycerides, cholesterol, or LDL and low HDL, increases cardiovascular risk. Tamarillo (Solanum betaceum Cav.) contains flavonoids and anthocyanins with potential lipid-lowering effects. This study evaluated the effect of ethanol extract of Tamarillo fruit (ETB) at doses of 100 mg/kg body weight (BW)/day and 200 mg/kg BW/day on triglyceride levels in Wistar rats with dyslipidemia, compared with simvastatin at 10 mg/kg BW/day. A posttest-only control group design was applied using 25 male Wistar rats divided into five groups: negative control, positive control, ETB 100, ETB 200, and simvastatin. Dyslipidemia was induced with a high-fat diet and propylthiouracil for 14 days, followed by 14 days of treatment. Triglyceride levels were measured using the GPO-PAP method. Data were analyzed with the Shapiro–Wilk test, Levene’s test, and Kruskal–Wallis test. The results showed no statistically significant differences between groups (p > 0.05). However, ETB at 200 mg/kg BW/day demonstrated a 22.6% reduction in triglyceride levels compared with the positive control, though the effect was slightly less than simvastatin. In conclusion, Tamarillo ethanol extract did not significantly reduce triglyceride levels but showed a favorable trend at higher doses, indicating potential for further research with dose optimization, longer duration, and standardized active compounds.   DOI : 10.35990/amhs.v4n2.p51-60   REFERENCES PERKENI. Pengelolaan Dislipidemia di Indonesia 2021. Jakarta: PB PERKENI; 2021. Nasution IS, Rahmadani AD, Audina W, Sari DP, Sari ND. Ulasan sistematis: Pengaruh gaya hidup dan pengetahuan masyarakat terhadap risiko penyakit jantung koroner. Sehat Rakyat: Jurnal Kesehatan Masyarakat. 2025;4(2):287–298. Siregar MH, Fatmah F, Sartika R. Analisis faktor utama kadar trigliserida abnormal pada penduduk dewasa di Indonesia. Jurnal Delima Harapan. 2020;7(2):118–127. Yuliana AR, Martha A. Efek pemberian seduhan kulit buah naga merah (Hylocereus polyrhizus) terhadap kadar trigliserida tikus Sprague Dawley dislipidemia. Journal of Nutrition College. 2016;5(4):428–437. Puspaseruni K. Tatalaksana dislipidemia terkait penyakit kardiovaskular aterosklerosis (ASCVD): Fokus pada penurunan LDL-C. Cermin Dunia Kedokteran. 2021;48(10):395–401. Sasmita, Djabir YY, Yustisia I. Efek pemberian dangke terhadap kadar kolesterol dan trigliserida darah tikus model hiperkolesterolemia dan hipertrigliseridemia. Majalah Farmasi dan Farmakologi. 2023;27(2):43–46. Fahmi NF, Laili NN. Differences in triglyceride levels between tobacco smokers and e-cigarette smokers. Proceedings of the National Seminar of Poltekkes Karya Husada Yogyakarta. 2019;1(1):79–88. Saragih AD. Terapi dislipidemia untuk mencegah risiko penyakit jantung koroner. Indonesian Journal of Nursing and Health Sciences. 2020;1(1):15–24. Udin B, Kholifah E. Literature review: Mechanism of action of antidyslipidemia drugs. Journal of Pharmaceutical Sciences. 2023;6(1):35–44. Dwi Sandhiutami NM, Khairani S, Moordiani M, Purpranoto IN. Efek sari buah terong Belanda (Solanum betaceum Cav.) terhadap perubahan profil lipid pada mencit dislipidemia. PHARMACY: Jurnal Farmasi Indonesia. 2021;18(2):226–234. Betaceum O, Riana I, Rahmawati P, Retnowati E, Devi RK. Judul tidak lengkap. 2020;5:7–13. Fairudz A, Nisa K. Pengaruh serat pangan terhadap kadar kolesterol penderita overweight. Medical Journal of Lampung University. 2015;4(8):121–126. Panche AN, Diwan AD, Chandra SR. Flavonoids: An overview. Journal of Nutritional Science. 2016;5:e47. Widiasriani IPA, Udayani NNW, Triansyah GAP, Dewi NPEM, Wulandari NLWE, Prabandari AASS. The role of flavonoid antioxidants in inhibiting free radicals. Jurnal Syifa Science and Clinical Research. 2024;6(2):188–197. Oktarini NWOAC, Dewi P, Puspawati NM, Swantara IMD, Astiti IAR, Rita WS. Antioxidant activity of flavonoid compounds in ethanol extract of Dutch eggplant seeds (Solanum betaceum) in inhibiting lipid peroxidation in Wistar rat blood. Adriana UH, Nofita, Marcelia S. Testing the combination activity of ethanol extracts from basil leaves (Ocimum × africanum Lour.) and fragrant pandan (Pandanus amaryllifolius Roxb.) as antibacterials against Salmonella typhi. Jurnal Malahayati. 2024. Liao CJ, Huang PS, Chien HT, Lin TK, Yeh CT, Lin KH. Effects of thyroid hormones on lipid metabolism pathologies in non-alcoholic fatty liver disease. Biomedicines. 2022;10(6):1–17. Ramadhani A, Hidayatt R, Khaira DS. The effect of ramania leaf ethanol extract on insulin and GDP in obese type 2 diabetes mice. Media Penelitian dan Pengembangan Kesehatan. 2025;35(1):143–156. Sinaga H, et al. Judul tidak lengkap. 2009. Kumalaningsih S. Antioksidan Alami: Penangkal Radikal Bebas, Sumber, Manfaat, Cara Penyediaan dan Pengolahan. Surabaya: Trubus Agrisarana; 2006. Whitcomb DC. Methods for measurement of serum lipids and lipoproteins. In: Rifai N, Warnick GR, Dominiczak MH, editors. Handbook of Lipoprotein Testing. 2nd ed. Washington DC: AACC Press; 2000. p. 115–126. Usmadi. Testing of analytical requirements (homogeneity test and normality test). Inovasi Pendidikan. 2020;7(1):50–62. Andra Ningsih D, Nurhasanah, Fadillah L. The effectiveness of outdoor learning in building students’ self-confidence in science lessons in grade V at SDN 190 Cenning. Journal of Basic Education and Teaching. 2019;4(2):1–12. Mishra P, Pandey CM, Singh U, Gupta A, Sahu C, Keshri A. Descriptive statistics and normality tests for statistical data. Annals of Cardiac Anaesthesia. 2019;22(1):67–72. Mishra P, Singh U, Pandey CM, Mishra P, Pandey G. Application of Student’s t-test, analysis of variance, and covariance. Annals of Cardiac Anaesthesia. 2019;22(4):407–411. Mohammed A, Samara F, Alzaatreh A, Knuteson SL. Statistical analysis for water quality assessment: A case study of Al Wasit Nature Reserve. Water (Switzerland). 2022;14(19):1–19. Rozi F, Irma, Maulidiya D. Analysis of inflation changes in several major cities in Indonesia using the Kruskal–Wallis test. Multi Proxima Journal of Statistics, Universitas Jambi. 2022;1(2):103–115. Naaktgeboren CA, Ochodo EA, Van Enst WA, De Groot JAH, Hooft L, Leeflang MMG, et al. Evaluation of result variability in systematic reviews of diagnostic studies. BMC Medical Research Methodology. 2016;16(1):1–8. Sudisma IGN, Soma IG, Sudira IW, Rastiti NM. Clinical and physiological responses of white rats (Rattus norvegicus) administered with Datura metel L. flower extract as anesthesia. Journal of Veterinary Science. 2023;41(3):323–335.